Xcast Based Routing Protocol For Push To Talk Application In Mobile Ad Hoc Networks - Al-Zyoud, Faisal Yousef Abed-alrahman (2011)
Mobile ad-hoc networks comprise a type of wireless network that can be easily created without the need for network infrastructure or administration. These networks are organized and administered into temporary and dynamic network topologies. Unfortunately, mobile ad-hoc networks suffer from some limitations related to insufficient bandwidth. The proliferation of new IP Multimedia subsystem services (IMs), such as Push-to-talk (PTT) applications consume large amounts of bandwidth, resulting in degraded QoS performance of mobile ad-hoc networks. In this thesis, a Priority XCAST based routing protocol (P-XCAST) is proposed for mobile ad-hoc networks to minimize bandwidth consumption. P-XCAST is based on demand route requests and route reply mechanisms for every destination in the PXCAST layer. To build the network topology and fill up the route table for nodes, the information in the route table is used to classify the XCAST list of destinations according to similarities on their next hop. Furthermore, P-XCAST is merged with a proposed Group Management algorithm to handle node mobility by classifying nodes into two types: group head and member. The proposed protocol was tested using the GloMoSim network simulator under different network scenarios to investigate Quality of Service (QoS) performance network metrics. P-XCAST performance was better by about 20% than those of other tested routing protocols by supporting of group size up to twenty receivers with an acceptable QoS. Therefore, it can be applied under different network scenarios (static or dynamic). In addition Link throughput and average delay was calculated using queuing network model; as this model is suitable for evaluating the IEEE 802.11 MAC that is used for push to talk applications. The analytical results for link throughput and average delay were used to validate the simulated results.